2018
DOI: 10.1093/toxsci/kfy025
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Dietary Exposure to Copper and Its Cellular Mechanisms Linking to Alzheimer’s Disease

Abstract: Metals are commonly found in the environment, household, and workplaces in various forms, and a significant segment of the population is routinely exposed to the trace amount of metals from variety of sources. Exposure to metals, such as aluminum, lead, iron, and copper, from environment has long been debated as a potential environmental risk factor for Alzheimer's disease (AD) for decades, yet results from in vitro, in vivo, and human population remain controversial. In the case of copper, the neurotoxic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…New risk factors have also been identified including those associated with diet such as obesity [31,71,125,185], diabetes [4,118,124] and factors associated with the immune system [12,128,141,158]. With reference to metal exposure, the case for aluminium is less strong but other metals such as zinc and copper have been implicated, and the interactions among different metals emphasised [16,86,147,156]. Recent data have also increased the probability that exposure to infectious agents could be involved [89].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New risk factors have also been identified including those associated with diet such as obesity [31,71,125,185], diabetes [4,118,124] and factors associated with the immune system [12,128,141,158]. With reference to metal exposure, the case for aluminium is less strong but other metals such as zinc and copper have been implicated, and the interactions among different metals emphasised [16,86,147,156]. Recent data have also increased the probability that exposure to infectious agents could be involved [89].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1980s, there has been more general concern regarding metal exposure as the ability of cells to efficiently maintain key processes with age, such as energy production, repair, and regeneration, is dependent on a range of metals [156]. In addition, a significant proportion of the population are routinely exposed to trace metals such as aluminium, lead, iron, and copper, obtained from a variety of sources, and all are potential risk factors for AD [86]. Arsene et al [16], however, reported no relationship between metal accumulation with age or neurodegeneration suggesting the brain was not a favourable site for metal accumulation.…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintained Cu 2+ exposure is possibly linked to the development of Alzheimer's disease through formation of Cu 2+ -amyloid-beta complex and promotion of a microglial pro-inflammatory M1 phenotype as opposed to an antiinflammatory M2 phenotype associated with Cu + (Hsu, Bondy, & Kitazawa, 2018). First, while it would have been interesting to resolve the disposition and chemical reactions of the acetate ions in vivo including possible changes of pH in the peri-implant tissue, these aspects are difficult to address by experimental methods and beyond the aims of the study.…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind that the study has a number of limitations. First, while it would have been interesting to resolve the dispo- (Hsu, Bondy, & Kitazawa, 2018). A more general concern regarding a possible use of Cu for impregnation of biomaterials which has to be carefully considered is the risk of accumulation to critical concentrations in the environment similar to other metals like mercury, lead, zinc, or cadmium, causing coselection of antibiotic resistance in bacteria (Imran, Das, & Naik, 2019).…”
Section: Discussionmentioning
confidence: 99%